1994
DOI: 10.1046/j.1471-4159.1994.62020582.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D1 and D2 Receptors and Their Signal System Present in Coated Vesicles Prepared from Bovine Striatal Tissue

Abstract: Coated vesicles (CVs) isolated from bovine striatal tissue were examined to determine whether they are associated with dopamine signal systems consisting of dopamine D, and D Z receptors, G proteins, and adenylate cyclase . Dopamine receptors in CVs were characterized by a dopamine D, receptor antagonist, [3 H]SCH 23390, and a dopamine D2 receptor antagonist, [ 3 H]spiroperidol . The bindings of both ligands were specifically saturable and reversible with a dissociation constant (K p) of 0 .65 and 0 .5 nM, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…[11] have shown that the density order of the receptors was dopamine D 1 > α 1 adrenergic > dopamine D 2 ≥ β 1 adrenergic receptors. This dopaminergic control has been also demonstrated in other tissue, for example, SKF‐38393, a D 1 ‐receptor agonist stimulated adenylate cyclase activity in coated vesicles isolated from bovine striatal tissues and inhibited by dopamine D 2 ‐receptor agonists [25]. Furthermore, functional interaction between melatonin and dopamine D 1 ‐receptors was reported in the retina [26], which indicated a link through the intracellular cyclic AMP system.…”
Section: Discussionmentioning
confidence: 68%
“…[11] have shown that the density order of the receptors was dopamine D 1 > α 1 adrenergic > dopamine D 2 ≥ β 1 adrenergic receptors. This dopaminergic control has been also demonstrated in other tissue, for example, SKF‐38393, a D 1 ‐receptor agonist stimulated adenylate cyclase activity in coated vesicles isolated from bovine striatal tissues and inhibited by dopamine D 2 ‐receptor agonists [25]. Furthermore, functional interaction between melatonin and dopamine D 1 ‐receptors was reported in the retina [26], which indicated a link through the intracellular cyclic AMP system.…”
Section: Discussionmentioning
confidence: 68%